Climate Change and Agriculture : A Review of Impacts and Adaptations - Kurukulasuriya, Pradeep; Rosenthal, Shane (World Bank, Washington, DC, 2014)
The vulnerability of the agricultural sector to both climate change and variability is well established in the literature. The general consensus is that changes in temperature and precipitation will result in changes in land and water regimes that will subsequently affect agricultural productivity. Research has also shown that specifically in tropical regions, with many of the poorest countries, impacts on agricultural productivity are expected to be particularly harmful. The vulnerability of these countries is also especially likely to be acute in light of technological, resource, and institutional constraints. Although estimates suggest that global food production is likely to be robust, experts predict tropical regions will see both a reduction in agricultural yields and a rise in poverty levels as livelihood opportunities for many engaged in the agricultural sector become increasingly susceptible to expected climate pressures